2018
DOI: 10.1165/rcmb.2017-0404oc
|View full text |Cite
|
Sign up to set email alerts
|

The Microbiome Regulates Pulmonary Responses to Ozone in Mice

Abstract: Previous reports demonstrate that the microbiome impacts allergic airway responses, including airway hyperresponsiveness, a characteristic feature of asthma. Here we examined the role of the microbiome in pulmonary responses to a nonallergic asthma trigger, ozone. We depleted the microbiota of conventional mice with either a single antibiotic (ampicillin, metronidazole, neomycin, or vancomycin) or a cocktail of all four antibiotics given via the drinking water. Mice were then exposed to room air or ozone. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
80
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(88 citation statements)
references
References 54 publications
7
80
1
Order By: Relevance
“…Our data (127) indicate that the microbiome also plays a role in the asthma-like phenotype of mice to the non allergic asthma trigger, ozone. However, this role is different from the role of the microbiome in allergic airways disease models.…”
Section: Mechanistic Basis For the Role Of Obesity In Severe Asthmamentioning
confidence: 71%
See 1 more Smart Citation
“…Our data (127) indicate that the microbiome also plays a role in the asthma-like phenotype of mice to the non allergic asthma trigger, ozone. However, this role is different from the role of the microbiome in allergic airways disease models.…”
Section: Mechanistic Basis For the Role Of Obesity In Severe Asthmamentioning
confidence: 71%
“…SCFAs enter the blood stream and alter both intestinal and bone marrow immune cells ultimately altering the dendritic cells that are required for allergen-mediated immune responses in the lungs. SCFAs also appear to contribute to the role of the microbiome in ozone-induced AHR in mice, though the role of SCFAs differs in this non allergic model (127). …”
Section: Mechanistic Basis For the Role Of Obesity In Severe Asthmamentioning
confidence: 99%
“…Results are the mean + SE of 4-7 mice/group. # p < 0.05 versus chow fed mice with same genotype and housing; % p < 0.05 versus WT mice with same diet and housing; $ p < 0.05 versus same housed mice with the same diet and genotype the lung microbiome because previous data from our lab suggest that it is the gut and not the lung microbiome that accounts for the role of the microbiome in pulmonary responses to ozone [33]. In chow-fed same housed mice, the Simpson index, a measure of ecological diversity, was significantly lower in ST2-deficient than WT same housed (Fig.…”
Section: Effect Of St2 Deficiency and Cohousing On The Gut Microbial mentioning
confidence: 95%
“…Androgen‐induced changes in the microbiome could also be involved in O 3 ‐induced AHR. We have reported that antibiotics and germ‐free conditions both attenuate O 3 ‐induced AHR in male mice (Cho et al, ) and that sex differences in O 3 ‐induced AHR are abolished after antibiotic treatment (Cho et al, ). There are sex differences in the gut microbiome (Cho et al, ) , (Markle et al, ) that only appear after puberty (Markle et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…We have reported that antibiotics and germ‐free conditions both attenuate O 3 ‐induced AHR in male mice (Cho et al, ) and that sex differences in O 3 ‐induced AHR are abolished after antibiotic treatment (Cho et al, ). There are sex differences in the gut microbiome (Cho et al, ) , (Markle et al, ) that only appear after puberty (Markle et al, ). Furthermore, castration has been shown to alter the gut microbiome (Markle et al, ; Org et al, ).…”
Section: Discussionmentioning
confidence: 99%